PENGARUH RETURN ON ASSET, RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM (Studi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2012-2015) - Dina Kurniawaningsih (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
The purpose of this research is to identify the influence of return on asset, return on equity, and debt to equity ratio on thestock price of mining companies during the period of 2012-2015. The independent variables of this study are return on asset, return on equity, and debt to equity ratio. The dependent variable of this study is stock price. This quantitative research is an explanatory research, which explains the relation or influence among variables. This research uses secondary data taken from the financial data available in the Indonesia Stock Exchange, written in the companies’ financial report. This research uses a sample of 10 companies, selected through purposive sampling method. The variables were tested using Multiple Linear Regression. The results indicate that return on equity and debt to equity ratio significantly influence the stock price. Nevertheless, return on asset does not influence the stock price.Keywords: return on asset, return on equity, debt to equity ratio, stock price